Positive electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2024012711
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-16
- Filing Date
- 2024-01-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2040-01-16
AI Technical Summary
Lithium transition metal oxides with high nickel content face increased battery resistance at low temperatures due to the high cost of cobalt, necessitating a solution that suppresses resistance while maintaining capacity.
A lithium transition metal oxide with a layered structure containing Ni, Nb, and tetravalent metal elements, along with external additive particles of W, B, or Al on the surface, within specific compositional and structural parameters to stabilize the layered structure and reduce resistance.
The solution effectively suppresses battery resistance at low temperatures and maintains capacity by optimizing the composition and structure of the lithium transition metal oxide, ensuring stability and performance.
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a technique for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] 2. Description of the Related Art In recent years, non-aqueous electrolyte secondary batteries have been widely used as high-output, high-energy density secondary batteries. The non-aqueous electrolyte secondary batteries include a positive electrode, a negative electrode, and a non-aqueous electrolyte, and are charged and discharged by transferring lithium ions or the like between the positive electrode and the negative electrode.
[0003] As positive electrode active materials used in the positive electrode of non-aqueous electrolyte secondary batteries, for example, the following are known.
[0004] For example, Patent Document 1 discloses a compound represented by the formula 1: Li x Ni 1-y-z-v-w Co y AlzM 1 v M 2 w O2, and the element M in formula 1 1 is at least one selected from the group consisting of Mn, Ti, Y, Nb, Mo and W, and the element M in the formula 1 2 are at least two elements selected from the group consisting of Mg, Ca, Sr and Ba, and the element M 2 contains at least Mg and Ca, and formula 1 satisfies 0.97≦x≦1.1, 0.05≦y≦0.35, 0.005≦z≦0.1, 0.0001≦v≦0.05, and 0.0001≦w≦0.05.
[0005] Furthermore, for example, Patent Document 2 discloses a positive electrode active material for a nonaqueous electrolyte secondary battery, the composition of which is represented by the following formula (I), and which contains at least one element selected from Mo, W, Nb, Ta, and Re in a proportion of 0.1 mol % or more and 5 mol % or less with respect to the total molar amount of Mn, Ni, and Co in formula (I).
[0006] [L]3a [M] 3b [O2] 6c …(I) (However, in the above formula (I), L is an element containing at least Li, M is an element containing at least Ni, Mn, and Co, or Li, Ni, Mn, and Co, 0.4 ≤ molar ratio of Ni / (Mn + Ni + Co) < 0.7 0.1 < molar ratio of Mn / (Mn + Ni + Co) ≤ 0.4 0.1 ≤ molar ratio of Co / (Mn + Ni + Co) ≤ 0.3 and the molar ratio of Li in M is 0 or more and 0.05 or less) [Prior Art Documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Application Laid-Open No. 2006-310181 [Patent Document 2] Japanese Patent Application Laid-Open No. 2009-289726 [Summary of the Invention] [Problems to be Solved by the Invention]
[0008] By the way, lithium transition metal oxides in which the proportion of Ni is 90 mol% or more and less than 100 mol% with respect to the total amount of metal elements excluding Li are expected as cathode active materials showing high battery performance, but there is a problem that the battery resistance increases at low temperatures. To improve the increase in battery resistance at low temperatures, for example, as in Patent Document 1, it is preferable to add 5 mol% or more of Co. However, since cobalt is expensive, it is desired to suppress the content of Co from the viewpoint of manufacturing cost.
[0009] Therefore, an object of the present disclosure is to provide a cathode active material and a non-aqueous electrolyte secondary battery capable of suppressing an increase in battery resistance at low temperatures even when the content of Co is suppressed in a lithium transition metal oxide in which the proportion of Ni is in the range of 90 mol% or more and less than 100 mol% with respect to the total amount of metal elements excluding Li.
Means for Solving the Problem
[0010] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure has a layered structure, and includes a lithium transition metal oxide containing Ni, Nb, a metal element having a valence of 4 or more other than Nb, and optional Co, and at least one element selected from W, B, and Al, and external addition particles adhering to the particle surface of the lithium transition metal oxide. The ratio of Ni to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 90 mol% ≤ Ni < 100 mol%. The ratio of Nb to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 0 mol% < Nb ≤ 3 mol%. The ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of Co ≤ 2.0 mol%. The ratio of metal elements other than Li present in the Li layer of the layered structure is in the range of 1 mol% or more and 2.5 mol% or less with respect to the total amount of metal elements excluding Li in the lithium transition metal oxide. The lithium transition metal oxide has a half-value width n of the diffraction peak of the (208) plane in the X-ray diffraction pattern by X-ray diffraction in the range of 0.30° ≤ n ≤ 0.50°. The ratio of W, B, and Al in the external addition particles to the total amount of the lithium transition metal oxide is in the range of 0.01 mol% or more and 0.3 mol% or less.
[0011] A non-aqueous electrolyte secondary battery according to one aspect of the present disclosure includes a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery described above.
Advantages of the Invention
[0012] According to one aspect of the present disclosure, in a lithium transition metal oxide in which the ratio of Ni is in the range of 90 mol% or more and less than 100 mol% with respect to the total amount of metal elements excluding Li, even if the Co content is suppressed, an increase in battery resistance at low temperatures can be suppressed.
Embodiments for Carrying Out the Invention
[0013] The positive electrode active material for a non-aqueous electrolyte secondary battery, which is one aspect of the present disclosure, has a layered structure and includes a lithium transition metal oxide containing Ni, Nb, a metal element having a valence of 4 or more other than Nb, and optional Co, and an externally added particle containing at least one element among W, B, and Al and adhering to the particle surface of the lithium transition metal oxide. The ratio of Ni to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 90 mol% ≤ Ni < 100 mol%. The ratio of Nb to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 0 mol% < Nb ≤ 3 mol%. The ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of Co ≤ 2.0 mol%. The ratio of the metal element other than Li present in the Li layer of the layered structure is in the range of 1 mol% or more and 2.5 mol% or less with respect to the total amount of metal elements excluding Li in the lithium transition metal oxide. The lithium transition metal oxide has a half-value width n of the diffraction peak of the (208) plane in the X-ray diffraction pattern by X-ray diffraction in the range of 0.30° ≤ n ≤ 0.50°. The ratio of W, B, and Al in the externally added particles to the total amount of the lithium transition metal oxide is in the range of 0.01 mol% or more and 0.3 mol% or less.
[0014] Usually, in a lithium transition metal oxide in which the proportion of Ni is in the range of 90 mol% or more and less than 100 mol% with respect to the total amount of metal elements excluding Li, if the content of Co is 2 mol% or less, there is a problem that the battery resistance of a non-aqueous electrolyte secondary battery at low temperatures increases. However, as in one embodiment of the present disclosure, when external particles containing at least one element of W, B, and Al are attached to the particle surface of a lithium transition metal oxide containing Nb, it is considered that electronic interaction occurs between at least one element of W, B, and Al and Nb, improving the state of the particle surface of the lithium transition metal oxide. As a result, the increase in battery resistance at low temperatures is suppressed. However, if the content of Nb in the lithium transition metal oxide becomes too high, a lot of divalent Ni will be present in the layered structure of the lithium transition metal oxide, and the layered structure will become unstable, and the battery capacity may decrease. In addition, if the proportions of W, B, and Al in the external particles with respect to the total amount of the lithium transition metal oxide are too high, Li in the lithium transition metal oxide may be extracted, resulting in a decrease in battery capacity. Therefore, by setting the Nb content in the lithium transition metal oxide and the ratios of W, B and Al in the external additive particles relative to the amount of lithium transition metal oxide within the ranges specified in one embodiment of the present disclosure, it is possible to not only suppress an increase in battery resistance at low temperatures, but also to suppress a decrease in battery capacity.
[0015] Furthermore, as in one embodiment of the present disclosure, the lithium transition metal oxide contains a tetravalent or higher metal element other than Nb, and a predetermined amount of a metal element other than Li is present in the Li layer of the layered structure, which is believed to further stabilize the layered structure, making it possible to suppress, for example, a decrease in battery capacity. Also, as in one embodiment of the present disclosure, the half-width of the diffraction peak of the (208) plane in the X-ray diffraction pattern by X-ray diffraction is within the above-mentioned predetermined range, which is believed to cause a moderate fluctuation in the arrangement between the Li layer and the transition metal layer of the layered structure, leading to stabilization of the layered structure, making it possible to suppress, for example, a decrease in battery capacity.
[0016] Hereinafter, an example of a nonaqueous electrolyte secondary battery using the positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure will be described.
[0017] The nonaqueous electrolyte secondary battery, which is an example of the embodiment, includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. It is preferable to provide a separator between the positive electrode and the negative electrode. Specifically, the battery has a structure in which a wound electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, and a nonaqueous electrolyte are housed in an outer casing. The electrode body is not limited to a wound electrode body, and other types of electrode bodies may be applied, such as a laminated electrode body in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween. In addition, the type of the nonaqueous electrolyte secondary battery is not particularly limited, and examples thereof include a cylindrical type, a square type, a coin type, a button type, and a laminate type.
[0018] The positive electrode, negative electrode, nonaqueous electrolyte, and separator used in the nonaqueous electrolyte secondary battery, which is one example of the embodiment, will be described in detail below.
[0019] <Positive electrode> The positive electrode is composed of a positive electrode current collector such as a metal foil and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface layer. The positive electrode active material layer includes, for example, a positive electrode active material, a binder, a conductive material, etc.
[0020] The positive electrode is obtained, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, etc., onto a positive electrode current collector, drying the slurry, thereby forming a positive electrode active material layer on the positive electrode current collector, and then rolling the positive electrode active material layer.
[0021] The positive electrode active material includes a lithium transition metal oxide having a layered structure and containing Ni, Nb, a metal element having a valence of 4 or more other than Nb, and an optional element Co, and external additive particles containing at least one element of W, B, and Al and attached to the particle surface of the lithium transition metal oxide. Hereinafter, the lithium transition metal oxide having a layered structure and containing Ni, Nb, a metal element having a valence of 4 or more other than Nb, and an optional element Co is referred to as the "lithium transition metal oxide of this embodiment."
[0022] The layered structure of the lithium transition metal oxide of this embodiment includes, for example, a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, and the like. Among these, a layered structure belonging to the space group R-3m is preferable in terms of high capacity, stability of the layered structure, and the like.
[0023] The ratio of Ni to the total amount of metal elements excluding Li in the lithium transition metal oxide of this embodiment may be in the range of 90 mol% ≤ Ni < 100 mol%, but in terms of increasing the capacity of the battery and the like, it is preferably in the range of 92 mol% ≤ Ni ≤ 96 mol%.
[0024] The ratio of Nb to the total amount of metal elements excluding Li in the lithium transition metal oxide of this embodiment may be in the range of 0 mol% < Nb ≤ 3 mol% in terms of suppressing the increase in battery resistance at low temperatures, etc., but preferably in the range of 0.2 mol% ≤ Nb ≤ 2.0 mol%, more preferably in the range of 0.2 mol% ≤ Nb ≤ 1.5 mol%. Even if the content of Nb exceeds 3 mol%, it is possible to suppress the increase in battery resistance at low temperatures, but since a large amount of unstable divalent Ni exists in the layered structure, the layered structure may become unstable and the battery capacity may decrease.
[0025] The ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide of this embodiment may be in the range of Co ≤ 2 mol%, but in terms of manufacturing cost, it is preferably in the range of Co ≤ 1.0 mol%, and more preferably Co = 0.0 mol%.
[0026] Examples of the tetravalent or higher metal elements other than Nb in the lithium transition metal oxide of this embodiment include Ti, Mn, Sn, Zr, Si, Mo, W, Ta, V, and Cr. When the lithium transition metal oxide contains a tetravalent or higher metal element other than Nb, the layered structure is more stabilized, which leads to suppression of a decrease in battery capacity. Among the above-listed metal elements, Mn and Ti are preferred, and Mn is particularly preferred, from the viewpoint of suppressing a decrease in battery capacity. The content of the tetravalent or higher metal element other than Nb is preferably 1 mol% to 5 mol% with respect to the total amount of metal elements other than Li in the lithium transition metal oxide of this embodiment.
[0027] The lithium transition metal oxide of the present embodiment may contain Li, Ni, Nb, a tetravalent or higher metal element other than Nb, and Co, as well as other metal elements other than the above-mentioned metal elements, such as Al, Fe, Mg, Cu, Na, K, Ba, Sr, Bi, Be, Zn, Ca, and B. Among these, Al and Fe are preferred, and Al is particularly preferred, from the viewpoint of suppressing a decrease in battery capacity.
[0028] The content of elements constituting the lithium transition metal oxide of this embodiment can be measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0029] In the lithium transition metal oxide of this embodiment, metal elements other than Li are present in the Li layer of the layered structure. The ratio of metal elements other than Li present in the Li layer of the layered structure is in the range of 1 mol % to 2.5 mol % and preferably in the range of 1 mol % to 2 mol % with respect to the total amount of metal elements other than Li in the lithium transition metal oxide in order to suppress a decrease in battery capacity, etc. The metal elements other than Li present in the Li layer of the layered structure are mainly Ni, based on the ratio of elements constituting the lithium transition metal oxide of this embodiment, but other metal elements may also be present.
[0030] The proportion of metal elements other than Li present in the Li layer of the layered structure can be obtained from the results of Rietveld analysis of the X-ray diffraction pattern obtained by X-ray diffraction measurement of the lithium transition metal oxide of this embodiment.
[0031] The X-ray diffraction pattern is obtained by a powder X-ray diffraction method using a powder X-ray diffractometer (manufactured by Rigaku Corporation, product name "RINT-TTR", radiation source Cu-Kα) under the following conditions. Measurement range: 15-120° Scan speed: 4° / min Analysis range: 30-120° Background; B-spline Profile function; split pseudo-Voigt function Constraint condition; Li(3a) + Ni(3a)=1 Ni(3a) + Ni(3b) = y y is the ratio of Ni to the total amount of metal elements other than Li in the lithium transition metal oxide (0.90≦y<1.00) ICSD No.;98-009-4814 In addition, the Rietveld analysis of the X-ray diffraction pattern is performed using the Rietveld analysis software PDXL2 (Rigaku Corporation).
[0032] In the lithium transition metal oxide of this embodiment, the half-width n of the diffraction peak of the (208) plane in the X-ray diffraction pattern by the X-ray diffraction is in the range of 0.30°≦n≦0.50°, and preferably in the range of 0.30°≦n≦0.45°, in order to suppress a decrease in battery capacity, etc. If the half-width n of the diffraction peak of the (208) plane is outside the above range, the fluctuation in the arrangement between the Li layer and the transition metal layer in the layered structure may be too small or too large, reducing the stability of the layered structure and causing a decrease in battery capacity.
[0033] In the lithium transition metal oxide of the present embodiment, the lattice constant a indicating the a-axis length of the crystal structure obtained from the result of the X-ray diffraction pattern by the X-ray diffraction is preferably in the range of 2.870 Å≦a≦2.877 Å, and the lattice constant c indicating the c-axis length is preferably in the range of 14.18 Å≦c≦14.21 Å. When the lattice constant a is smaller than 2.870 Å, the atomic distance in the crystal structure may become narrower and more unstable than when the above range is satisfied, and the battery capacity may decrease. When the lattice constant a is larger than 2.877 Å, the atomic distance in the crystal structure may become wider and more unstable, and the battery capacity may decrease compared to when the above range is satisfied. When the lattice constant c is smaller than 14.18 Å, the atomic distance in the crystal structure may become narrower and more unstable, and the battery capacity may decrease compared to when the above range is satisfied. When the lattice constant c is larger than 14.21 Å, the atomic distance in the crystal structure may become wider and more unstable, and the battery capacity may decrease compared to when the above range is satisfied.
[0034] The lithium transition metal oxide of this embodiment has a crystallite size s calculated from the half-width of the diffraction peak of the (104) plane in the X-ray diffraction pattern by the Scherrer equation in the range of 400 Å≦s≦700 Å, preferably 400 Å≦s≦550 Å. If the crystallite size s of the lithium transition metal oxide of this embodiment is outside the above range, the stability of the layered structure decreases, and the battery capacity may decrease compared to when the above range is satisfied. The Scherrer equation is expressed by the following formula.
[0035] s=Kλ / Bcosθ In the formula, s is the crystallite size, λ is the wavelength of the X-ray, B is the half-width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is set to 0.9.
[0036] The content of the lithium transition metal oxide in this embodiment is preferably 90 mass % or more, and more preferably 99 mass % or more, based on the total mass of the positive electrode active material, for example, from the viewpoint of improving charge / discharge efficiency.
[0037] The positive electrode active material of the present embodiment may contain other lithium transition metal oxides in addition to the lithium transition metal oxide of the present embodiment, such as lithium transition metal oxides having a Ni content of 0 mol % to less than 90 mol %.
[0038] As described above, the positive electrode active material of this embodiment contains at least one of W, B, and Al, and has external particles attached to the particle surface of the lithium transition metal oxide of this embodiment. The particle surface refers to at least one of the surface of the secondary particles formed by aggregation of primary particles and the surface of the primary particles inside the secondary particles. In other words, the external particles are attached to the surface of the secondary particles of the lithium transition metal oxide, the surface of the primary particles inside the secondary particles, or both surfaces. The surface of the secondary particles is synonymous with the surface of the primary particles present on the surface of the secondary particles.
[0039] The external particles containing at least one of W, B, and Al are, for example, at least one of external particles containing W, B, and Al, external particles containing W and B, external particles containing W and Al, external particles containing B and Al, external particles containing W, external particles containing B, and external particles containing Al.
[0040] The external particles containing at least one of W, B, and Al are, for example, an oxide or a salt thereof containing at least one of W, B, and Al. The external particles containing W are, for example, WO 2、 Examples of the external particles containing B include tungsten oxide such as WO3 and W2O5, and salts of tungsten oxide such as lithium tungstate. Examples of the external particles containing B include boron oxide such as B2O3, and salts of boron oxide such as lithium borate. Examples of the particles containing Al include aluminum oxide such as Al2O3. The external particles are not limited to oxides or their salts, and may be nitrides, hydroxides, carbonates, sulfates, phosphates, nitrates, etc.
[0041] The content of the external particles containing at least one of W, B and Al may be 0.01 mol% or more and 0.3 mol% or less in terms of the ratio of W, B and Al in the external particles to the total amount of the lithium transition metal oxide of this embodiment, but is preferably 0.05 mol% or more and 0.3 mol% or less, more preferably 0.05 mol% or more and 0.25 mol% or less. If the ratio of W, B and Al is less than 0.01 mol%, the effect of suppressing the increase in battery resistance at low temperatures cannot be obtained. In addition, even if the ratio of W, B and Al exceeds 0.3 mol%, it is possible to suppress the increase in battery resistance at low temperatures, but lithium in the lithium transition metal oxide may be extracted, resulting in a decrease in battery capacity.
[0042] An example of a method for producing the lithium transition metal oxide of this embodiment will be described.
[0043] The method for producing a lithium transition metal oxide of this embodiment preferably includes a multi-stage firing process including a first firing process in which a mixture containing a compound containing a tetravalent or higher metal element other than Ni and Nb and other optional metal elements (Co, Al, etc.), a Li compound, and a Nb-containing compound is fired in a firing furnace under oxygen flow at a first heating rate to a first set temperature of 450 ° C. to 680 ° C., and a second firing process in which the fired product obtained by the first firing process is fired in a firing furnace under oxygen flow at a second heating rate to a second set temperature of more than 680 ° C. to 800 ° C. Here, the first heating rate is in the range of 1.5 ° C. / min to 5.5 ° C. / min, and the second heating rate is slower than the first heating rate and is preferably in the range of 0.1 ° C. / min to 3.5 ° C. / min. Such multi-step calcination makes it easier to adjust the ratio of metal elements other than Li present in the Li layer of the layered structure of the lithium transition metal oxide of this embodiment, the half-width n of the diffraction peak of the (208) plane, the lattice constant a, the lattice constant c, the crystallite size s, and other parameters within the above-specified ranges than in a single-step calcination. The first and second calcination steps are described in detail below.
[0044] The compound containing a metal element having a valence of 4 or more other than Ni and Nb and an arbitrary metal element used in the first firing step is, for example, an oxide containing a metal element having a valence of 4 or more other than Ni and Nb and an arbitrary other metal element (Co, Al, etc.). The oxide can be obtained, for example, by dropping an alkaline solution such as sodium hydroxide into a solution of a metal salt containing a metal element having a valence of 4 or more other than Ni and Nb and an arbitrary other metal while stirring the solution, adjusting the pH to the alkaline side (for example, 8.5 to 14.0), and precipitating (co-precipitating) the compound hydroxide containing a metal element having a valence of 4 or more other than Ni and Nb and an arbitrary other metal, and firing the compound hydroxide. The firing temperature is not particularly limited, but is, for example, in the range of 400°C to 600°C.
[0045] The Li compound used in the first firing step is, for example, lithium hydroxide, lithium carbonate, etc. The Nb-containing compound used in the first firing step is, for example, niobium oxide, lithium niobate, niobium chloride, etc., and niobium oxide is particularly preferred. By using these raw materials, a lithium transition metal oxide with high battery performance can be obtained.
[0046] The tetravalent or higher metal elements other than Ni and Nb and the arbitrary metal element-containing compound used in the lithium transition metal oxide manufacturing method of the present embodiment do not contain Nb, and it is preferable that the Nb-containing compound does not contain other metal elements such as Ni. By using these raw materials, a lithium transition metal oxide with high battery performance can be obtained.
[0047] In the mixture used in the first firing step, the mixing ratio of the compound containing Ni and any metal element, the Li compound, and the Nb-containing compound may be set appropriately. However, it is preferable that the molar ratio of metal elements other than Li:Li is in the range of 1:0.98 to 1:1.08, because this makes it easy to adjust each parameter, such as the ratio of metal elements other than Li present in the Li layer of the layered structure of the lithium transition metal oxide, the half-width n of the diffraction peak of the (208) plane, the lattice constant a, the lattice constant c, and the crystallite size s, within the above-specified ranges.
[0048] The first set temperature in the first firing step is preferably in the range of 450°C to 680°C, more preferably in the range of 550°C to 680°C, in order to adjust each of the parameters of the lithium transition metal oxide to the ranges specified above. The first heating rate in the first firing step is preferably in the range of 1.5°C / min to 5.5°C / min, more preferably in the range of 2.0°C / min to 5.0°C / min, in order to adjust each of the parameters of the lithium transition metal oxide to the ranges specified above. Note that the first heating rate may be set multiple times for each temperature range as long as it is within the range specified above. The firing start temperature (initial temperature) in the first firing step is, for example, in the range of room temperature to 200°C.
[0049] The holding time of the first set temperature in the first firing step is preferably from 0 to 5 hours, more preferably from 0 to 3 hours, in order to adjust each of the parameters of the lithium transition metal oxide within the ranges specified above. The holding time of the first set temperature refers to the time during which the first set temperature is maintained after reaching the first set temperature.
[0050] The second set temperature in the second firing step is preferably in the range of more than 680°C and not more than 800°C, more preferably in the range of 680°C or more and not more than 750°C, in terms of adjusting each of the parameters of the lithium transition metal oxide to the ranges specified above. The second heating rate in the second firing step is preferably slower than the first heating rate, and is in the range of 0.1°C / min or more and not more than 3.5°C / min, more preferably in the range of 0.2°C / min or more and not more than 2.5°C / min, in terms of adjusting each of the parameters of the lithium transition metal oxide to the ranges specified above. Note that the second heating rate may be set multiple times for each temperature range as long as it is within the range specified above. For example, when the first set temperature is less than 680°C, the second heating rate may be divided into a heating rate A from the first set temperature to 680°C and a heating rate B from 680°C to the second set temperature. It is preferable that the heating rate B in the latter stage is slower than the heating rate A in the former stage.
[0051] The holding time of the second set temperature in the second firing step is preferably from 1 hour to 10 hours, more preferably from 1 hour to 5 hours, in order to adjust each of the parameters of the lithium transition metal oxide within the ranges specified above. The holding time of the second set temperature is the time for which the second set temperature is maintained after reaching the second set temperature.
[0052] In the oxygen stream in the multi-stage calcination process, the above-mentioned parameters of the lithium transition metal oxide are adjusted to fall within the above-specified ranges. For example, the oxygen concentration in the oxygen stream is set to 60% or more, and the flow rate of the oxygen stream is set to 10 cm 3 The range of the flow rate is preferably 0.2 mL / min to 4 mL / min per kg of the mixture and 0.3 L / min or more per kg of the mixture. Furthermore, the maximum pressure applied inside the firing furnace is preferably in the range of 0.1 kPa to 1.0 kPa in addition to the pressure outside the firing furnace.
[0053] Examples of methods for attaching external particles containing at least one metal element selected from W, B, and Al to the particle surface of the lithium transition metal oxide of this embodiment include wet methods such as a method of adding a solution in which a compound containing at least one metal element selected from W, B, and Al is dissolved or dispersed to a suspension containing the lithium transition metal oxide of this embodiment, or a method of adding (e.g., spraying) a solution in which a compound containing at least one metal element selected from W, B, and Al is dissolved or dispersed while mixing particles of the lithium transition metal oxide of this embodiment, and a dry method in which particles of the lithium transition metal oxide of this embodiment and particles of a compound containing at least one metal element selected from W, B, and Al are mixed.
[0054] By using the above-mentioned method, the external particles containing at least one metal element selected from W, B, and Al can be attached to the particle surface of the lithium transition metal oxide of this embodiment. The lithium transition metal oxide particles to which the external particles containing at least one metal element selected from W, B, and Al are attached are preferably heat-treated at, for example, 100°C or more and 400°C or less. If the temperature is less than 100°C, the adhesion of the external particles containing at least one metal element selected from W, B, and Al is low, and the amount of the external particles detached from the particle surface of the lithium transition metal oxide may increase. If the temperature exceeds 400°C, the ratio of metal elements other than Li present in the Li layer of the layered structure of the lithium transition metal oxide of this embodiment may increase, and the battery capacity may decrease.
[0055] Other materials contained in the positive electrode active material layer will be described below.
[0056] Examples of the conductive material contained in the positive electrode active material layer include carbon powders such as carbon black, acetylene black, ketjen black, and graphite. These may be used alone or in combination of two or more.
[0057] Examples of the binder contained in the positive electrode active material layer include fluorine-based polymers, rubber-based polymers, etc. Examples of the fluorine-based polymers include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), or modified versions of these, and examples of the rubber-based polymers include ethylene-propylene-isoprene copolymers, ethylene-propylene-butadiene copolymers, etc. These may be used alone or in combination of two or more.
[0058] <Negative electrode> The negative electrode includes a negative electrode current collector such as a metal foil and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode current collector may be a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface layer. The negative electrode active material layer includes, for example, a negative electrode active material, a binder, a thickener, and the like.
[0059] The negative electrode is obtained, for example, by applying a negative electrode mixture slurry containing a negative electrode active material, a thickener, and a binder onto a negative electrode current collector, followed by drying to form a negative electrode active material layer on the negative electrode current collector, and then rolling the negative electrode active material layer.
[0060] The negative electrode active material contained in the negative electrode active material layer is not particularly limited as long as it is a material capable of absorbing and releasing lithium ions, and examples thereof include carbon materials, metals capable of forming an alloy with lithium, or alloy compounds containing such metals. Examples of carbon materials include graphites such as natural graphite, non-graphitizable carbon, and artificial graphite, and cokes. Examples of alloy compounds include those containing at least one metal capable of forming an alloy with lithium. Examples of elements capable of forming an alloy with lithium include silicon and tin, and silicon oxide and tin oxide, which are formed by combining these with oxygen, can also be used. In addition, a mixture of the carbon material and a compound of silicon or tin can be used. In addition to the above, a material having a charge / discharge potential with respect to metallic lithium, such as lithium titanate, higher than that of the carbon material can also be used.
[0061] The binder contained in the negative electrode active material layer may be, for example, a fluoropolymer, a rubber-based polymer, or the like, as in the case of the positive electrode, but styrene-butadiene copolymer (SBR) or a modified product thereof may also be used. The binder contained in the negative electrode active material layer may be, for example, a fluororesin, PAN, a polyimide resin, an acrylic resin, a polyolefin resin, or the like, as in the case of the positive electrode. When preparing the negative electrode mixture slurry using an aqueous solvent, it is preferable to use styrene-butadiene rubber (SBR), CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K, or the like, or a partially neutralized salt), polyvinyl alcohol (PVA), or the like.
[0062] Examples of the thickener contained in the negative electrode active material layer include carboxymethyl cellulose (CMC), polyethylene oxide (PEO), etc. These may be used alone or in combination of two or more.
[0063] <Non-aqueous electrolyte> The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (non-aqueous electrolyte solution), and may be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.
[0064] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.
[0065] Examples of the above ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ether, etc., and chain ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.
[0066] As the above halogenated derivatives, it is preferable to use fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylic acid esters such as methyl fluoropropionate (FMP), etc.
[0067] The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic lithium carboxylates, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more} and other imide salts. The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the non-aqueous solvent.
[0068] <separator> The separator may be, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator may be made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin, or a separator having an aramid resin or the like applied to its surface. A filler layer containing an inorganic filler may be formed at the interface between the separator and at least one of the positive electrode and the negative electrode. Examples of the inorganic filler include oxides containing at least one of titanium (Ti), aluminum (Al), silicon (Si), and magnesium (Mg), phosphate compounds, and those whose surfaces are treated with hydroxides or the like. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode, the negative electrode, or the separator. EXAMPLES
[0069] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.
[0070] <Example 1> [Preparation of positive electrode active material] Composite oxide containing Ni, Co, Al and Mn (Ni0.91 Co 0.01 Al 0.04 Mn 0.04 A mixture was obtained by mixing Ni, Nb, Co, Al, and Mn, LiOH, and Nb2O3 so that the molar ratio of the total amount of Ni, Nb, Co, Al, and Mn to Li was 1:1.03. The mixture was placed in a sintering furnace and heated under an oxygen flow (10 cm) with an oxygen concentration of 95%. 3 The mixture was fired at a temperature rise rate of 2.0°C / min from room temperature to 650°C, and then fired at a temperature rise rate of 0.5°C / min from 650°C to 710°C under a flow rate of 2 mL / min per kg of mixture and 5 L / min per kg of mixture. The fired product was washed with water to obtain a lithium transition metal oxide. This was the lithium transition metal oxide of Example 1. The proportions of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 1 were as shown in Table 1.
[0071] In addition, the lithium transition metal oxide of Example 1 was subjected to powder X-ray diffraction measurement under the conditions described above to obtain an X-ray diffraction pattern. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.8 mol %, the half-width of the diffraction peak of the (208) plane was 0.48°, the lattice constant a was 2.872 Å, the lattice constant c was 14.20 Å, and the crystallite size s was 459 Å.
[0072] Pure water was added to the lithium transition metal oxide particles of Example 1, and the mixture was stirred and then filtered and separated to prepare the lithium transition metal oxide with a moisture content adjusted to 5%, and WO3 powder was added so that the ratio of W element to the lithium transition metal oxide was 0.1 mol%, followed by heat treatment at 180°C. When the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 1.
[0073] <Example 2> A lithium transition metal oxide was prepared in the same manner as in Example 1, except that in the positive electrode active material preparation method of Example 1, WO3 powder was replaced with H3BO3 powder. The proportions of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 2 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 2, diffraction lines indicating a layered structure were confirmed, the proportion of metal elements other than Li present in the Li layer was 1.6 mol%, and the half-width of the diffraction peak of the (208) plane was 0.45°.
[0074] In addition, when the obtained powder was analyzed by SEM-EDX, it was found that particles containing boron were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 2.
[0075] <Example 3> A lithium transition metal oxide was prepared in the same manner as in Example 1, except that in the positive electrode active material preparation method of Example 1, WO3 powder was replaced with Al2(SO4)3 powder. The proportions of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 3 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 3, diffraction lines indicating a layered structure were confirmed, the proportion of metal elements other than Li present in the Li layer was 2.2 mol%, and the half-width of the diffraction peak of the (208) plane was 0.48°.
[0076] In addition, when the obtained powder was analyzed by SEM-EDX, it was found that aluminum-containing particles were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 3.
[0077] <Example 4> A lithium transition metal oxide was prepared in the same manner as in Example 1, except that in the positive electrode active material preparation method of Example 1, in addition to WO3 powder, Al2(SO4)3 powder was added so that the ratio of Al element to the lithium transition metal oxide was 0.05 mol%. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 4 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 4, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 2.3 mol%, and the half-width of the diffraction peak of the (208) plane was 0.49°.
[0078] In addition, when the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten and particles containing aluminum were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 4.
[0079] <Example 5> In the positive electrode active material preparation method of Example 1, in addition to WO3 powder, H3BO3 powder was added so that the ratio of B element to the lithium transition metal oxide was 0.1 mol%, and Al2(SO4)3 powder was added so that the ratio of Al element to the lithium transition metal oxide was 0.05 mol%. A lithium transition metal oxide was prepared in the same manner as in Example 1. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 5 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 5, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 2.4 mol%, and the half-width of the diffraction peak of the (208) plane was 0.5°.
[0080] In addition, when the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten, particles containing boron, and particles containing aluminum were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 5.
[0081] <Example 6> A lithium transition metal oxide was prepared in the same manner as in Example 1, except that in the positive electrode active material preparation method of Example 1, in addition to WO3 powder, H3BO3 powder was added so that the ratio of B element to the lithium transition metal oxide was 0.1 mol%. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 6 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 6, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 2 mol%, and the half-width of the diffraction peak of the (208) plane was 0.44°.
[0082] In addition, when the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten and particles containing boron were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 6.
[0083] <Example 7> In the positive electrode active material preparation method of Example 1, a lithium transition metal oxide was prepared in the same manner as in Example 1, except that the WO3 powder was replaced with H3BO3 powder, and the H3BO3 powder was added so that the ratio of B element to the lithium transition metal oxide was 0.01 mol%. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 7 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 7, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.5 mol%, and the half-width of the diffraction peak of the (208) plane was 0.43°.
[0084] In addition, when the obtained powder was analyzed by SEM-EDX, it was found that particles containing boron were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 7.
[0085] <Example 8> Composite oxide containing Ni, Co, Al and Mn (Ni 0.91 Co 0.01 Al 0.04 Mn0.04 A lithium transition metal oxide was produced in the same manner as in Example 1, except that 1.02O2), LiOH, and Nb2O3 were mixed so that the molar ratio of Li to the total amount of Ni, Nb, Co, Al, and Mn was 1:1.03, and the molar ratio of Nb to the total amount of Ni, Co, Al, and Mn in the composite oxide containing Ni, Co, Al, and Mn was 100:0.05. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 8 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 8, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.7 mol%, and the half-width of the diffraction peak of the (208) plane was 0.39 °.
[0086] In addition, the lithium transition metal oxide particles of Example 8 were added with WO3 powder in the same manner as in Example 1, and then heat-treated at 180°C. When the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 8.
[0087] <Example 9> Composite oxide containing Ni, Co, Al and Mn (Ni 0.905 Co 0.015 Al 0.05 Mn 0.03 A lithium transition metal oxide was produced in the same manner as in Example 1, except that 1.02O2), LiOH, and Nb2O3 were mixed so that the molar ratio of Li to the total amount of Ni, Nb, Co, Al, and Mn was 1:1.03. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 9 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 9, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.4 mol%, and the half-width of the diffraction peak of the (208) plane was 0.47°.
[0088] In addition, the lithium transition metal oxide particles of Example 9 were added with WO3 powder in the same manner as in Example 1, and then heat-treated at 180°C. When the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 9.
[0089] <Example 10> Composite oxide containing Ni, Co, Al and Mn (Ni 0.915 Co 0.01 Al 0.5 Mn 0.025 A lithium transition metal oxide was produced in the same manner as in Example 1, except that 1.02O2), LiOH, and Nb2O3 were mixed so that the molar ratio of Li to the total amount of Ni, Nb, Co, Al, and Mn was 1:1.03. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Example 10 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 10, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.6 mol%, and the half-width of the diffraction peak of the (208) plane was 0.5°.
[0090] In addition, the lithium transition metal oxide particles of Example 10 were added with WO3 powder in the same manner as in Example 1, and then heat-treated at 180°C. When the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 10.
[0091] <Example 11> Composite oxide containing Ni, Co, Al and Mn (Ni 0.92 Al 0.05 Mn 0.03A lithium transition metal oxide was produced in the same manner as in Example 1, except that 1.0O2), LiOH, and LiNbO3 were mixed so that the molar ratio of Li to the total amount of Ni, Nb, Al, and Mn was 1:1.03. The ratios of Ni, Al, Mn, and Nb in Example 11 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Example 11, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.8 mol%, and the half-width of the diffraction peak of the (208) plane was 0.38°.
[0092] In addition, the lithium transition metal oxide particles of Example 11 were added with WO3 powder in the same manner as in Example 1, and then heat-treated at 180°C. When the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Example 11.
[0093] <Comparative Example 1> In the positive electrode active material preparation method of Example 1, a lithium transition metal oxide was prepared in the same manner as in Example 1, except that WO3 powder was not added. The proportions of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Comparative Example 1 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Comparative Example 1, a diffraction line indicating a layered structure was confirmed, and the proportion of metal elements other than Li present in the Li layer was 2.8 mol%, the half-width of the diffraction peak of the (208) plane was 0.48°, the lattice constant a was 2.873 Å, the lattice constant c was 14.20 Å, and the crystallite size s was 488 Å. The lithium transition metal oxide of Comparative Example 1 was used as the positive electrode active material of Comparative Example 1.
[0094] <Comparative Example 2> Composite oxide containing Ni, Co, Al and Mn (Ni 0.91 Co 0.01 Al 0.04 Mn 0.04A positive electrode active material was prepared in the same manner as in Example 1, except that 1,02) and LiOH were mixed so that the molar ratio of Li to the total amount of Ni, Co, Al and Mn was 1:1.03, and WO3 powder was not added. The ratios of Ni, Co, Al and Mn in the lithium transition metal oxide of Comparative Example 2 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Comparative Example 2, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.6 mol%, the half-width of the diffraction peak of the (208) plane was 0.41°, the lattice constant a was 2.872 Å, the lattice constant c was 14.20 Å, and the crystallite size s was 479 Å. Pure water was added to the particles of the lithium transition metal oxide of Comparative Example 2, and the mixture was stirred and filtered and separated, and the lithium transition metal oxide with the moisture content adjusted to 5% was heat-treated at 180°C. This was used as the positive electrode active material of Comparative Example 2.
[0095] <Comparative Example 3> A lithium transition metal oxide was prepared in the same manner as in Example 9, except that WO3 powder was not added in the positive electrode active material preparation method of Example 9. The proportions of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Comparative Example 3 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Comparative Example 3, diffraction lines indicating a layered structure were confirmed, the proportion of metal elements other than Li present in the Li layer was 1.8 mol%, and the half-width of the diffraction peak of the (208) plane was 0.42°. The lithium transition metal oxide of Comparative Example 3 was used as the positive electrode active material of Comparative Example 3.
[0096] <Comparative Example 4> Composite oxide containing Ni, Co, Al and Mn (Ni 0.905 Co 0.015 Al 0.05 Mn 0.03A positive electrode active material was prepared in the same manner as in Example 9, except that 1.02) and LiOH were mixed so that the molar ratio of Li to the total amount of Ni, Co, Al and Mn was 1:1.03, and WO3 powder was not added. The ratios of Ni, Co, Al and Mn in the lithium transition metal oxide of Comparative Example 4 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Comparative Example 4, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.5 mol%, and the half-width of the diffraction peak of the (208) plane was 0.39°. Pure water was added to the particles of the lithium transition metal oxide of Comparative Example 4, and the mixture was stirred and filtered and separated, and the lithium transition metal oxide with the moisture content adjusted to 5% was heat-treated at 180°C. This was used as the positive electrode active material of Comparative Example 4.
[0097] <Comparative Example 5> A lithium transition metal oxide was prepared in the same manner as in Example 10, except that WO3 powder was not added in the positive electrode active material preparation method of Example 10. The proportions of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Comparative Example 5 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Comparative Example 5, diffraction lines indicating a layered structure were confirmed, the proportion of metal elements other than Li present in the Li layer was 1.2 mol%, and the half-width of the diffraction peak of the (208) plane was 0.44°. The lithium transition metal oxide of Comparative Example 5 was used as the positive electrode active material of Comparative Example 5.
[0098] <Comparative Example 6> A lithium transition metal oxide was prepared in the same manner as in Example 11, except that WO3 powder was not added in the positive electrode active material preparation method of Example 11. The proportions of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Comparative Example 6 were as shown in Table 1. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Comparative Example 6, diffraction lines indicating a layered structure were confirmed, the proportion of metal elements other than Li present in the Li layer was 1.8 mol%, and the half-width of the diffraction peak of the (208) plane was 0.48°. The lithium transition metal oxide of Comparative Example 6 was used as the positive electrode active material of Comparative Example 6.
[0099] <Reference example 1> Pure water was added to the lithium transition metal oxide particles of Example 1, and the mixture was stirred and then filtered and separated to prepare the lithium transition metal oxide with a moisture content adjusted to 5%, and WO3 powder was added so that the ratio of W element to the lithium transition metal oxide was 0.3 mol%, followed by heat treatment at 180°C. When the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Reference Example 1.
[0100] <Reference example 2> The lithium transition metal oxide particles of Example 1 were mixed with pure water, stirred, and then filtered and separated to prepare the lithium transition metal oxide with a moisture content adjusted to 5%, and WO3 powder was added so that the ratio of W element to the lithium transition metal oxide was 0.4 mol%, followed by heat treatment at 180°C. When the obtained powder was analyzed by SEM-EDX, it was found that particles containing tungsten were attached to the surface of the lithium transition metal oxide particles. This was used as the positive electrode active material of Reference Example 2.
[0101] <Reference example 3> Composite oxide containing Ni, Co, Al and Mn (Ni 0.925 Co 0.01 Al 0.055 Mn 0.01Lithium transition metal oxide was produced in the same manner as in Example 1, except that 100:0.5 molar ratio of Nb to the total amount of Ni, Co, Al, and Mn was 100:0.5, and that 100:0.5 molar ratio of Nb to the total amount of Ni, Co, Al, and Mn in the composite oxide containing Ni, Co, Al, and Mn was 100:0.5. The ratios of Ni, Co, Al, Mn, and Nb in the lithium transition metal oxide of Reference Example 3 were as shown in Table 3. In addition, as a result of performing powder X-ray diffraction measurement on the lithium transition metal oxide of Reference Example 3, diffraction lines showing a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 2.2 mol%, and the half-width of the diffraction peak of the (208) plane was 0.53°. WO3 powder was added to the particles of the lithium transition metal oxide of Reference Example 3 in the same manner as in Example 1, and then the particles were heat-treated at 180°C. The obtained powder was analyzed by SEM-EDX, and it was found that particles containing tungsten were attached to the surfaces of the lithium transition metal oxide particles. This was used as the positive electrode active material of Reference Example 3.
[0102] [Preparation of positive electrode] The positive electrode active material of Example 1 was mixed in a ratio of 95 parts by mass, 3 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder. The mixture was kneaded using a kneader (TK Hibismix, manufactured by Primix Corporation) to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to an aluminum foil having a thickness of 15 μm, and the coating was dried to form a positive electrode active material layer on the aluminum foil. This was the positive electrode of Example 1.
[0103] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0104] [Preparation of test cell] The positive electrode of Example 1 and the negative electrode made of lithium metal foil were laminated so as to face each other with a separator interposed therebetween, and the laminate was wound to prepare an electrode assembly. Next, the electrode assembly and the nonaqueous electrolyte were inserted into an aluminum exterior body to prepare a test cell.
[0105] Test cells for Examples 2 to 11, Comparative Examples 1 to 6, and Reference Examples 1 to 3 were prepared in the same manner.
[0106] (Evaluation of battery resistance at low temperatures) The test cells of each Example, Comparative Example, and Reference Example were charged to half of the initial capacity at a constant current of 0.5 It in a temperature environment of -10°C, and then the charging was stopped and left for 15 minutes. Then, the voltage was measured when the cells were charged for 10 seconds at a constant current of 0.1 It. After discharging the charge capacity for 10 seconds, the current value was changed and the cells were charged for 10 seconds, the voltage at that time was measured, and then the charge capacity for 10 seconds was discharged. The charge / discharge and voltage measurement were repeated at current values from 0.1 It to 2 It. The battery resistance was calculated from the relationship between the measured voltage value and current value.
[0107] (Battery capacity evaluation) The test cells of Example 1 and Reference Examples 1 to 3 were charged at a constant current of 1 It in an environment of 25° C. until the battery voltage reached 4.2 V, and then discharged at a constant current of 1 It until the battery voltage reached 2.5 V, and the discharge capacity (battery capacity) was determined.
[0108] Table 1 shows the evaluation results of the battery resistance at low temperatures for each Example and Comparative Example. Table 2 shows the evaluation results of the battery resistance and battery capacity at low temperatures for Example 1 and Reference Examples 1 and 2. Table 3 shows the evaluation results of the battery capacity for Example 1 and Reference Example 3.
[0109] [Table 1]
[0110] [Table 2]
[0111] [Table 3]
[0112] As can be seen from Table 1, in all of Examples 1 to 11 in which external particles containing at least one of W, B and Al were attached to the particle surface of lithium transition metal oxide containing Ni, Nb, and a metal element having a valence of 4 or more other than Nb, the battery resistance at low temperature was lower than that of Comparative Examples 1 to 6 in which external particles containing at least one of W, B and Al were not attached to the particle surface of lithium transition metal oxide containing a metal element having a valence of 4 or more other than Ni, Nb, and Nb. Also, as can be seen from Table 2, when the content of tungsten contained in the external particles was increased, the battery resistance at low temperature decreased, but the battery capacity also decreased. Also, as can be seen from Table 3, when the half-width of the diffraction peak of the (208) plane of the lithium transition metal oxide became 0.5° or more, the battery capacity decreased.
Claims
1. A lithium transition metal oxide having a layered structure and containing Ni, Nb, a tetravalent or higher metal element other than Nb, and an optional element Co, and external additive particles containing at least one element of W, B, and Al attached to the surface of the lithium transition metal oxide particles, The ratio of Ni to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 90 mol%≦Ni<100 mol%, The ratio of Nb to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 0 mol% < Nb ≦ 3 mol%, The ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of Co≦2 mol %; a ratio of metal elements other than Li present in the Li layer of the layered structure is in the range of 1 mol % to 2.5 mol % based on the total amount of metal elements other than Li in the lithium transition metal oxide, The lithium transition metal oxide has an X-ray diffraction pattern in which the half-width n of the diffraction peak of the (208) plane is in the range of 0.30°≦n≦0.50°, a ratio of W, B and Al in the external additive particles to a total amount of the lithium transition metal oxide is 0.01 mol % or more and 0.3 mol % or less.
2. 2. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal oxide has a lattice constant a indicating an a-axis length of a crystal structure and a lattice constant c indicating a c-axis length of a crystal structure obtained from an analysis result of an X-ray diffraction pattern by X-ray diffraction, the lattice constant a being in the range of 2.870 Å≦a≦2.877 Å and the lattice constant c being in the range of 14.18 Å≦c≦14.21 Å.
3. 3. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal oxide has a crystallite size s in the range of 400 Å≦s≦700 Å, the crystallite size s being calculated from a half-width of a diffraction peak of a (104) plane in an X-ray diffraction pattern by Scherrer's formula.
4. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for non-aqueous electrolyte secondary batteries according to any one of claims 1 to 3.